Implementasi Media Audio Visual Pada Pembelajaran PAI Dalam Meningkatkan Motivasi Belajar Siswa Di SMP Islam Terpadu Nurul Qur’an Tegalwaru Karawang Jawa Barat - Muhammad Sultan AL Husain; Laily Masruroh (Pusat Riset dan Inovasi Nasional, 2025)
Audio visual media in islamic religious education learning in schools as the main step to help create effective and efficient learning. Schools have an important role in making students who have noble morals and good character through the implementation of audio visual media in islamic religious education learning at smp islam terpadu nurul qur'an tegalwaru karawang west java.the focus of this study is to determine how the implementation of audio-visual media in islamic religious education learning at the integrated islamic junior high school nurul qur'an tegalwaru karawang, west java, how the learning motivation of students at the integrated islamic junior high school nurul qur'an tegalwaru karawang, west java, and how the implementation of audio-visual media in islamic religious education learning increases the learning motivation of students at the integrated islamic junior high school nurul qur'an tegalwaru karawang, west java.this research method uses a qualitative approach. This type of research is a case study. Then seen from the data collection techniques in this study using observation, interview, and documentation techniques. While the techniques in data analysis used are data reduction, data presentation, and drawing conclusions.the results of the research conducted by researchers regarding the implementation of audio-visual media in islamic religious education learning in increasing student learning motivation at smp islam terpadu nurul qur'an tegalwaru karawang west java. The implementation of audio-visual media in islamic religious education learning can help achieve the school's vision to become an educational institution that excels in academics and religion. The implementation of audio-visual media in islamic religious education learning using audio-visual media can increase student learning motivation and help students understand islamic religious education material more easily and effectively. The implementation of audio-visual media in islamic religious education learning in increasing student learning motivation can be a good step to help improve the quality of education and the reputation of educational institutions.